2013
DOI: 10.1111/apha.12184
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of acute hyperglycaemia on the rat heart

Abstract: Coordinate NOGP activation in response to acute hyperglycaemia results in contractile dysfunction during ischaemia-reperfusion, allowing for the development of novel cardioprotective agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 73 publications
7
42
1
Order By: Relevance
“…Moreover, a mouse model of diabetes and atherosclerosis lacking RAGE displayed significantly less aortic plaque area (312). Our laboratory and others also found increased AGE levels following ischemia and reperfusion in the absence of atherosclerosis (39,184,192,296), demonstrating more direct effects on rodent hearts. Such detrimental effects of elevated AGEs on cardiac contractile dysfunction are also much more pronounced under hyperglycemic conditions following ischemia-reperfusion (184,192).…”
Section: H156supporting
confidence: 54%
See 3 more Smart Citations
“…Moreover, a mouse model of diabetes and atherosclerosis lacking RAGE displayed significantly less aortic plaque area (312). Our laboratory and others also found increased AGE levels following ischemia and reperfusion in the absence of atherosclerosis (39,184,192,296), demonstrating more direct effects on rodent hearts. Such detrimental effects of elevated AGEs on cardiac contractile dysfunction are also much more pronounced under hyperglycemic conditions following ischemia-reperfusion (184,192).…”
Section: H156supporting
confidence: 54%
“…Polyol pathway inhibition also improved cardiac energy metabolism under normoglycemic and hyperglycemic conditions (241,242), attenuated oxidative stress, and restored electrolyte homeostasis (219,281,293,317). Moreover, data from our laboratory revealed that benfotiamine (a vitamin B 1 analog) treatment lowered polyol pathway activation and restored cardiac contractile function following ischemia-reperfusion under hyperglycemic conditions (192). However, the translation of experimental studies is lagging because some synthetic aldose reductase drugs have elicited deleterious side effects in clinical trials without showing significant beneficial effects (32).…”
Section: Hyperglycemia-induced Actation Of the Nogpsmentioning
confidence: 68%
See 2 more Smart Citations
“…) or metabolic substrate concentration (Mapanga et al . ). Oxidative stress is a major focus of physiological and pathophysiological studies (Heinonen et al .…”
mentioning
confidence: 97%